A modified leaf disk method for rearing predaceous mites [Acarina : Phytoseiidae] - Brodeur, J.; Cloutier, C. (Phytoprotection, 1992)
The detached leaf disk method for rearing phytoseiids was modified by maintaining leaf disks on a nutrient solution solidified with agar. The predaceous mite, Amblyseius cucumeris, and thrips prey, Frankliniella occidentalis, were successfully reared on cucumber leaf disks using this technique. Predator survival and retention time on agar as the leaf supporting medium were improved compared to cotton wool. Agar prolonged leaf disk quality for thrips survival compared to both cotton wool and water, while offering other significant advantages to these alternative media.